Developing Autoplay-Based Media for Learning Asking and Giving Suggestions at Senior High School - Sausan, Afra Dilla; Hidayat, Hendi (STIT Buntet Pesantren Cirebon, 2022)
The educational field has shifted from traditional classroom settings primarily using printed learning resources to a technological-based learning system. This study was intended to develop AutoPlay-based media for learning Asking and Giving Suggestions at Senior High School. The purpose of this study is to find out the characteristics of AutoPlay-based media and develop the AutoPlay-based media for learning speaking. This study employed a qualitative approach using the R&D method with ADDIE model. The primary data source for this study comes from journals, articles, books, and others while the secondary data comes from English teachers. The researcher gathered data through a literature review and interviews. The English teacher is a participant in this study. The result shows that there are 12 characteristics of AutoPlay-based media for learning speaking. They are: (1) learning media should combine audio and visual elements, (2) Learning objectives should be clearly stated in the media, (3) Media has a well-defined learning flow, (4) Media provides conclusions, examples, and evaluations for students, (5) Media can motivate students to learn, (6) Use language that students can easy to understand, (7) Materials contents should be consistent with the standard and fundamental competencies and relevant to the Curriculum 2013, (8) The content of the materials should be constantly updated, (9) The content of the materials should be applicable in a variety of contexts, (10) Learning media should be used to present materials in a timely manner while also stimulating students speaking skills, (11) Learning media should focus on the suitability of the speaking materials for students, and (12) Pay attention to aspects of speaking when assessing students' speaking skills. The AutoPlay-based media developed based on 12 characteristics have been found in the need analysis.